Persistent measles infection in malnourished children. - Dossetor, J (1977)
Thirty malnourished and 25 well-nourished children were studied six to 31 days after the onset of a measles rash. Evidence of the virus was found in 40% of the malnourished children but in none of the well-nourished controls. Giant cells were found in the nasal secretions of five out of 17 malnourished children and measles antigen was detected in the lymphocytes of eight out of 28. The malnourished children showed depressed cell-mediated immunity to measles and candida antigens and a low response to meningococcal vaccine. Fifteen died from intercurrent infections. Malnutrition was thought to have depressed the immune response in these children, resulting in a severe and prolonged attack of measles. This, in turn, led to further damage to the immune system and more severe malnutrition. Thus these children were made susceptible to intercurrent infection.